Kontribusi Sektor Perikanan dalam Pembangunan Wilayah Kabupaten Buton Tengah, Sulawesi Tenggara: Pendekatan Location Quotient (LQ) - Prihantini, Campina Illa; Rahmayana, Rahmayana; Nursalam, Nursalam (Universitas Galuh, 2024)
Buton Tengah Regency is one of the districts in Southeast Sulawesi Province which has quite large marine and fisheries resource potential. Its position in seventh place as a large capture fisheries producer in Southeast Sulawesi Province requires the government to be able to manage this potential optimally for the welfare of the community. This study aims to analyze the contribution of the fisheries sector as a leading sector in the development of the Buton Tengah Regency region. The data used is secondary data from the Gross Regional Domestic Product (GRDP) of Buton Tengah Regency 2016-2020 using the Location Quotient (LQ) analysis tool. The results of the LQ analysis show that the fisheries sector which is grouped into two sub-sectors can be categorized as basic and superior sectors for Buton Tengah Regency with a high level of specialization (cultivated fisheries sub-sector is 1.41 and capture fisheries sub-sector is 1.01). The results of this analysis show that the fisheries sector in Buton Tengah Regency has a competitive advantage (both aquaculture and capture fisheries sub-sectors) over the fisheries sector in Southeast Sulawesi Province. The recommended policy recommendations are: 1) increasing gross regional domestic product (GRDP) by developing a fisheries sector that is oriented towards markets outside the region or abroad; and 2) the fisheries sector needs to increase its competitiveness or competitive advantage through sustainable development of the fisheries industry (upstream - downstream).